Policy impact on institutions of federal financial transfers in Australia and India - Jha, Himanshu (2004)
In a federal democratic setup different formulae and policy framework are evolved for fiscal sharing between the Centre and States. Fiscal equilisation has been an important working principle for federal transfers. This article discusses in detail the institution arrangement for fiscal transfers in India and Australia and highlights similarities and dissimilarities in constitution and working of these institutions. It focusses on the steps that put thrust on macro-economic management and situation arising out of liberalisation policies. - Reproduced.
Keywords: Intergovernmental fiscal relations - Australia; Intergovernmental fiscal relations - India; Intergovernmental fiscal relations